Fundamental Modes of Operation for Mass Customization - MacCarthy, Bart L.; Brabazon, Philip G.; Bramham, Jo (Elsevier Science B.V., 2003)
The concept of Mass Customization (MC) - producing customised goods for a mass market - has received considerable attention in the research literature in recent years. However the literature is limited in providing an understanding of the content of MC strategies (the organizational structures, process technologies, etc., that are best in a particular environment) and the process of MC strategies (the sub-strategy that an enterprise should select and how they should go about implementing an MC strategy). In this paper six published classification schemes of relevance to Mass Customization are reviewed. The classification schemes are applied to five case studies of enterprises operating in an MC environment. The limitations of the schemes are analysed and their failure to distinguish key characteristics is highlighted. Analysis of the findings leads to the development of a taxonomy of operational modes for MC. Five fundamental modes of operation for Mass Customization are identified. These modes are described and justified and their application is illustrated by contrasting the information requirements of two modes. The potential of these modes to provide the foundations for detailed configurations models is discussed.